eje2marcusjj
eje2marcusjj
17-08-2016
Mathematics
contestada
solve for y. a(y+c) = b(y-c)
Respuesta :
dalendrk
dalendrk
17-08-2016
a(y + c) = b(y - c)
ay + ac = by - bc
ay - by = -bc - ac
(a - b)y = -bc - ac
y = (-bc - ac)/(a - b)
y = (bc + ac)/(b - a)
Answer Link
VER TODAS LAS RESPUESTAS ( 26+ )
ACCESS MORE
Otras preguntas
Which word or phrase is closest in meaning to the word disposal as it is used in the text? Still, the production, transportation, and disposal of plastic water
Write the equation of the line that through the points (3,3) and (-1,-5)
Which function has a vertex at (2, 6)? f(x) = 2|x – 2| – 6 f(x) = 2|x – 2| 6 f(x) = 2|x 2| 6 f(x) = 2|x 2| – 6.
Prove that For any set A,B,C (A×B)×C equivalence A×B×C equivalence A×(B×C).
What is the width of a triangle with a volume of 3.5, a height of 1.4, and a length of 2.5? (please respond quickly)
thesis statement on what NATO had against Vietnam.
How is muscular dystrophy contracted?
The question In the picture
What is the difference between Horlicks and Bournvita?Explain -,-
Thomas Edison's fascination with what invention inspired him to develop the phonograph?